Dilthey and Darwin Combined? 19th Century Geisteswissenschaft for 21st Century Cultural Science. Issue 1 (10th July 2018) - Herrmann-Pillath, Carsten
This paper explores the relevance of Dilthey's conceptualisation of the ' Geisteswissenschaften ' (human sciences) for Cultural Science. In a nutshell, I argue that Cultural Science is Dilthey plus Darwin. In this effort, I define the Geisteswissenschaften as 'performative sciences': Taking economics as an example, I show that the Geisteswissenschaften are sciences which are ontologically productive in creating and performing the object of their research. That means, they are inherently normative since they entail critical reflexivity as a major mode of research. Following Dilthey, Geisteswissenschaften are deeply historical, which implies that their disciplinary structure is evolving together with their objects. Therefore, I argue that the 19th century division of disciplines needs to be thoroughly overhauled in the 21st century, including the division between economics and sociology, which is a left-over from 19th century nation-state development. New disciplines, with Cultural Science and Technosphere Science as prime examples, must be established to cope with the challenges of our times: where human agency, culture and technology have blurred long-established boundaries separating nature, culture and society; where identity and meaning have become global, fluid, contested and reflexive phenomena; and where nature (the environment) and culture (cities) are inextricably interrelated in the dynamics of the emergent Anthropocene system.